Potential of cultivar and crop management to affect phytochemical content in winter‐grown sprouting broccoli (Brassica oleracea L. var. italica). (8th July 2013) - Reilly, Kim; Valverde, Juan; Finn, Leo; Rai, Dilip K; Brunton, Nigel; Sorensen, Jens C; Sorensen, Hilmer; Gaffney, Michael
Abstract BACKGROUND Variety and crop management strategies affect the content of bioactive compounds (phenolics, flavonoids and glucosinolates) in green broccoli (calabrese) types, which are cultivated during summer and autumn in temperate European climates. Sprouting broccoli types are morphologically distinct and are grown over the winter season and harvested until early spring. Thus they show considerable potential for development as an import substitution crop for growers and consumers during the 'hungry gap' of early spring. The present study investigated the effect of variety and management practices on phytochemical content in a range of sprouting broccoli varieties. RESULTS Yields were significantly higher in white sprouting broccoli varieties. Levels of phenolics and flavonoids were in the range 81.64–297.65 and 16.95–104.80 mg 100 g−1 fresh weight, respectively, depending on year and cultivar, and were highest in variety 'TZ 5052' in both years. In‐row spacing did not affect flavonoid content. Phenolic and flavonoid content generally increased with increasing floret maturity and levels were high in edible portions of the crop. Crop wastes (leaf and flower) contained 145.9–239.3 and 21.5–116.6 mg 100 g−1 fresh weight total phenolics and flavonoids, respectively, depending on cultivar, tissue and year. Climatic factors had a significant effect on phenolic and flavonoid content. Levels of total and some individual glucosinolates were higher in sprouting broccoli than in the green broccoli variety 'Ironman'. CONCLUSION Levels of total phenolics, flavonoids and glucosinolates are higher in sprouting than green broccoli types. Sprouting broccoli represents an excellent source of dietary bioactive compounds. © 2013 Society of Chemical Industry